The Mediterranean biotypes of Tylenchulus semipenetrans in Spanish citrus orchards - Verdejo-Lucas, Soledad; Sorribas, Francisco J.; Pons, J.; Forner Valero, Juan B.; Alcaide, Antonio (2017)
The reproductive potentials of fourteen citrus nematode (Tylenchulus semipenetrans) populations, collected from the principal citriculture areas of Spain, were compared on sour orange and Carrizo citrange. All citrus nematode populations were identified as the mediterranean biotype. Reproductive potentials varied greatly among nematode populations. The infectivity and reproduction of populations collected from the rhizosphere of Troyer or Carrizo citrange rootstocks were higher (P greater than or equal to 0.05) than those of populations collected from sour orange.